A Solution to the Sunni and Shia Conflict in Sampang Madura Using a Dynamic Game Theory - Muhammad Wakhid Musthofa; Mohamad Yusup (IAIN Ponorogo, 2021)
The conflict between Sunni and the Shia community in Nangkernang hamlet, Karang Gayam village, Omben district and Gading Laok hamlet, Blu'uran village, Karang Penang district, Sampang has been going on since 1990s. The Shia community is still forced to live in the Puspa Agro flats in Jemundo Sidoarjo. The problem that has not been resolved is that the Shiite community wants to return to their hometown but the Sunnis still insist on refusing them. This study tried to find a solution to the problem using a dynamic game theory approach. Researcher constructed a dynamic game based on Prisoner's Dilemma model which represented the situation of conflict between Shia and Sunni communities. The resulting model then was simulated in order to offer a solution that government could execute to end the conflict and repatriate the Shia community to their hometown. Based on the game simulation, it is recommended that the repatriation of the Shia community from Jemundo Sidoarjo will only be safe if at least 80% of Sunnis accept the Shia community.